2012
DOI: 10.5902/198050986612
|View full text |Cite
|
Sign up to set email alerts
|

Efeito competicional em testes de progênies de eucalipto

Abstract: RESUMOMuitos estudos têm recomendado o uso de parcelas pequenas na experimentação florestal, porém, não consideram o aumento da competição intergenotípica que isto acarreta e que pode resultar na seleção incorreta dos materiais genéticos. O objetivo deste trabalho foi o de avaliar sete covariáveis de competição sobre o caráter volume de madeira em dois testes de progênies de Eucalyptus spp. O delineamento utilizado foi de blocos casualizados, com seis repetições de 10 plantas. As sete covariáveis analisadas fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 2 publications
(2 reference statements)
0
11
0
3
Order By: Relevance
“…Arithmetic mean of the silvicultural characteristic of the alo competitive trees (PAVAN et al, 2012), belonging to different genetic material (equation 8), where Y j is the observed value of the alo competitive plant j and n the number of alo competitive plants.…”
Section: Alo Competition Mean (Mal)mentioning
confidence: 99%
See 4 more Smart Citations
“…Arithmetic mean of the silvicultural characteristic of the alo competitive trees (PAVAN et al, 2012), belonging to different genetic material (equation 8), where Y j is the observed value of the alo competitive plant j and n the number of alo competitive plants.…”
Section: Alo Competition Mean (Mal)mentioning
confidence: 99%
“…In forest field trials, it is mainly caused by the lack of space induced by high intraspecific density (LEONARDECZ-NETO et al, 2003). In which the growth of the individuals of the plot is correlated to its neighbors, due to the common micro environment (PAVAN et al, 2012). In linear plots, this competition can occur within the plots (inter-genotypic competition) or between the experimental plots (intragenotypic competition).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations